1992
DOI: 10.1203/00006450-199211000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methylxanthines on Diaphragmatic Fatigue in the Piglet

Abstract: ABSTRACT. Studies in adult animal and human subjects have suggested that the methylxanthine drugs can delay the onsGir attenuate the severity of diaphragmatic fatigue. We have investigated the effect of aminophylline and caffeine on the pressure-generating capacity of the fatigued diaphragm in 1-mo-old piglets. Measurements of ventilation, transdiaphragmatic pressure, blood gases and pH, diaphragmatic electromyogram, diaphragmatic pressurefrequency curve (PdiFC), diaphragmatic blood flow, and end-expiratory lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…danialou et al [22] showed that theophylline causes a significant vasodilatation on diaphragm arterioles. On the contrary, the study by Mayock et al [26] on animals reported that there was no change in diaphragmatic blood flow after aminophylline infusion. However, methylxantine-derived drugs are reported to weaken the intensity of diaphragmatic weakness or can delay the start.…”
Section: (N)mentioning
confidence: 51%
“…danialou et al [22] showed that theophylline causes a significant vasodilatation on diaphragm arterioles. On the contrary, the study by Mayock et al [26] on animals reported that there was no change in diaphragmatic blood flow after aminophylline infusion. However, methylxantine-derived drugs are reported to weaken the intensity of diaphragmatic weakness or can delay the start.…”
Section: (N)mentioning
confidence: 51%
“…It is known that elevated VE may increase the partial pressure of alveolar/muscular oxygen and consequently induce improvements in performance in endurance [11]. In certain investigations, they failed to observe these findings, because the acute use of caffeine during the performance of a submaximal exercise at steady state (i.e., above 75% the VO2max) revealed increases in diaphragm muscle fatigue [29,11]. Therefore, it does not seem prudent that fatigue of the diaphragm muscle could be associated to the findings observed in our study, because the fatigue installed in this muscle can promote significant reductions in the VE [11], and this was not observed (Figure 2 D, P>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that by inducing systemic vasodilation, theophylline may also increase diaphragmatic blood flow, and thereby improve diaphragmatic force. However, several studies have demonstrated that diaphragmatic blood flow failed to increase after aminophylline [35][36][37], even when animals were breathing against an inspiratory resistive load [36,37], thus, showing that aminophylline has no direct effect on diaphragmatic arterioles. Moreover, we recently compared in vivo the effects of aminophylline on canine diaphragm stimulated at functional residual capacity (FRC) and near total lung capacity (TLC) (producing a diaphragm shortening similar to that in the present in vitro study), and we observed results similar to those obtained in vitro [38].…”
Section: Discussionmentioning
confidence: 99%